Bacteriophage as a novel therapeutic approach for killing multidrug-resistant Escherichia coli ST131 clone - Shamsuzzaman, Md; Kim, Shukho; Kim, Jungmin (Frontiers in Microbiology, 2024)
The emergence of the multidrug-resistant (MDR) Escherichia coli ST131 clone has significantly impacted public health. With traditional antibiotics becoming less effective against MDR bacteria, there is an urgent need for alternative treatment options. This study aimed to isolate and characterize four lytic phages (EC.W2-1, EC.W2-6, EC.W13-3, and EC.W14-3) from hospital sewage water and determine their effectiveness against the ST131 clone. These phages demonstrated a broad host range, effectively lysing 94.4% of highly pathogenic E. coli ST131 isolates. Morphological observations and phylogenetic analysis indicate that EC.W2-1, and EC.W13-3 belong to the Tequatrovirus genus in the Straboviridae family, while EC.W2-6 and EC.W14-3 are part of the Kuravirus genus in the Podoviridae family. Phages remained stable at pH 2–10 for 4 h and below 80°C for 1 h. These four phages showed in vitro bacterial lytic activity at various MOIs (0.1–0.001). The one-step growth curve of phages exhibited a short latent period of approximately 10–20 min and a moderate burst size of 50–80 (pfu/cell). Phages’ genome size ranged from 46,325–113,909 bp, with G + C content of 35.1 –38.3%. No virulence or drug resistance genes were found, which enhanced their safety profile. In vivo, EC.W2-6 and EC.W13.3, along with their cocktail, fully protected against the ESBL-producing E. coli ST131 infection model in vivo. Combining these phages and a 3-day repeated single phage, EC.W13-3 significantly enhanced the survival rate of E. coli ST131 infected mice at low MOI (0.01–0.001). The in vivo effectiveness of the isolated phages and the EC.W2-6 and EC.W14-3 cocktail in highly reducing bacterial load CFU/g in multiple organs strongly supports their potential efficacy. Based on in vivo, in vitro, and genomic analyses, phages have been proposed as novel and suitable candidates for killing the pandemic ST131 clone.